METABOLIC MODULATION OF MYOBLAST DIFFERENTIATION: BIOPHYSICAL AND MITOCHONDRIAL ADAPTATIONS TO GLUCOSE AVAILABILITY - Tolebay, Aizhan (Nazarbayev University School of Sciences and Humanities, 2025)
Skeletal muscle differentiation involves extensive cellular and metabolic remodeling, yet the influence of nutrient availability on the biophysical and mitochondrial properties of myoblasts remains poorly understood and studied. In this study, the effects of low (5 mM) and high (25 mM) glucose conditions on myogenesis of C2C12 cells were investigated by assessing changes in differentiation efficiency, cortical stiffness, cytoskeletal organization, mitochondrial morphology, and mitochondrial reactive oxygen species (ROS) production. High glucose significantly enhanced myogenic differentiation, as demonstrated by increased fusion index and myosin heavy chain expression. Differentiation, regardless of glucose concentration, was accompanied by increased cortical stiffness, highlighting mechanical stiffening as a consistent hallmark of myogenesis. However, mitochondrial adaptations—such as increased total mitochondrial volume and elevated mitochondrial ROS—were more pronounced under high glucose, suggesting that metabolic remodeling is glucose-sensitive, unlike stiffness changes. No significant differences in mitochondrial morphology were observed in undifferentiated myoblasts between glucose conditions, indicating limited metabolic responsiveness prior to differentiation. Together, these findings uncover the connection between metabolic inputs and biomechanical cues during myogenesis and support the inclusion of cortical stiffening as a novel biophysical marker of muscle cell differentiation, with implications for tissue engineering and regenerative strategies.
Keywords: Myogenesis; cortical stiffness; ROS; mitochondria; type of access: embargo